PENGARUH KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN MEBEL PADA CV AULIA JATI INDOFURNI JEPARA - Dean Jeri Pratama; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2019)
The aims of this study to find out how the influence given by product quality, and word of mouth to the purchase decision of furniture products from CV Aulia Jati Indofurni 100 Respondents selected are consumers who already make purchasing decisions and will make purchasing decisions of furniture products from CV Aulia Jati Indofurniby using purpocive sampling technique. The methodology used to analyze primary data in this research is validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, and significance test (t and F test) with SPSS 16.0. The results showed simultaneously product quality, and word of mouth have a significant effect on purchasing decision equal to 52,8% while the balancing influenced by many factors product quality and word of mouth. Some recommendation to increase purchase decision is CV Aulia Jati Indofurni must have social media and then make content about furniture, and must upgrade the design of produt with modern era model.